The diving beetles of the Kuril Archipelago in the Far East of Russia (Coleoptera: Dytiscidae). - Nilsson, Anders N.; Minakawa, Noboru; Oberg, Pontus B. H. (Contributions to Entomology = Beiträge zur Entomologie, 1997)
The species of predaceous diving beetles (Coleoptera, Dytiscidae) ocurring in the Kuril Archipelago in the northwest Pacific are reviewed. Based on literature records, the study of museum collections, and material from recent expeditions 24 species are known from the archipelago. A detailed report is given on the 357 adult and 50 larval specimens collected in the South and Mid Kuril Islands by the joint American-Japanese-Russian expeditions in 1994 and 1995. The following five species are here recorded from the Kurils for the first time: Hydroporus uenoi Nakane, Platambus pictipennis (Sharp), Agabus japonicus Sharp, Ilybius nakanei Nilsson, and Graphoderus zonatus (Hoppe). The number of species recorded on individual islands ranged from 1 to 11, with the largest islands at either end of the Greater Kuril Ridge being the most diverse. The South Kurils are dominated by Ussurian-Japanese species known also from Sakhalin and Hokkaido, whereas the North Kuril fauna includes a high proportion of Holarctic or Palearctic species known also from Kamchatka.